Progress in combination vaccines and the co-administration of influenza virus and SARS-CoV-2 vaccines - Hu, Chengyu; Niu, Chenguang; Li, Xiaohui; He, Ke; Li, Mengyu; Gao, Xiaonan; Wei, Qiannan; Sun, Weiyang; Zhao, Yongkun; Li, Yuanguo; Xia, Xianzhu; Ren, Zhiguang; et al. (Frontiers in Immunology, 2025)
COVID-19 and seasonal influenza have taken a huge toll on the global economy and global health. Given the potential of COVID-19 to transform into a chronic epidemic akin to seasonal influenza, the influenza virus and SARS-CoV-2 will continue to be a significant threat to healthcare for some time to come. Coinfection involving the two viruses has been proven to worsen the severity of the illness, as evidenced by clinical observational data. Vaccination remains the most effective measure in the prevention and treatment of infectious diseases. In addition, the coadministration of influenza virus and SARS-CoV-2 vaccines offered greater benefits than either vaccine alone. Combination vaccines are also a major hotspot in novel vaccine development. This review highlights the advancements in the development of combined vaccines for COVID-19 and seasonal influenza, as demonstrated in animal studies and clinical trials, and emphasizes the importance of a combined vaccine.